COMPARATIVE EFFICACY OF NORGESTOMET-BASED ESTROUS INDUCTION PROTOCOLS IN BEETAL GOAT - DOGRA, P; DHALIWAL, GS; SINGHAL, S; KASWAN, S (The Indian Journal of Animal Reproduction, 2016)
Sixty post-partum anestrus beetal goats were randomly divided into three groups of 20 each to compare the efficacy of norgestomet with or without prostaglandin (PGF2α) or eCG or both. Each goat subcutaneously received half norgestomet implant (1.5 mg) for 11 days either with eCG 500 IU on day 9 (Gp Norg+eCG), with PGF2α 50 μg on day 10 (Gp Norg+PG) or with both eCG and PG on day 9 and 10 of protocol, respectively (Gp Norg+eCG+PG). Subsequent to implant removal, estrus was detected twice a day using aproned buck and animals in estrus were mated twice at 12 h interval. Among the groups, highest estrus response (p>0.05) and minimum time to onset of estrus (p0.05) between groups. Conception rate and total kids varied between groups in the range of 57.9 to 83.3% and 19 to 28, respectively, with highest (p
Keywords: Anestrus; Beetal goats; Conception rate; Estrus induction; Norgestomet